Предмет: Алгебра,
автор: Kmilla2016
4). Упростите выражение:
( 6х – х^2 )^2 – х^2( х – 1 )( х + 1 ) + 6х( 3 + 2х^2 ).
ПОМОГИТЕ ПОЖАЛУЙСТА
Ответы
Автор ответа:
0
36x^2 - 12x^3 + x^4 - x^2(x^2-1) +18x + 12x^3= 36x^2 + x^4 - x^4 + x^2 +18x= 37x^2+18x=x(37x+18)
Автор ответа:
0
Спасибо. )
Автор ответа:
0
(6x-x^2)^2-x^2(x-1)(x+1)+6x(3+2x^2)=36x^2-12x^3+x^4-x^4+x^2+18x+12x^3=37x^2+18x=x(37x+18)
Автор ответа:
0
Спасибо. )
Похожие вопросы
Предмет: Литература,
автор: yuliyaa14
Предмет: Қазақ тiлi,
автор: kabuldanurzhan2005
Предмет: Математика,
автор: nastyahertz2006
Предмет: Алгебра,
автор: goddess471